Something's got to give : balancing work, childcare, and eldercare - Duxbury, Linda; Higgins, Christopher Alan (University of Toronto Press, 2017)
"A perfect storm of factors are brewing that will redefine dependent care in the coming decades. Delayed marriage and parenthood, longer life-spans, lower birthrates, and the health policy shift to informal caregiving have drastically increased the number of employees whose mental and physical health suffers due to an inability to balance work, childcare, and eldercare. Employers also feel the pinch as this inability to balance a myriad of demands is negatively impacting their bottom line. Something's Got to Give is a comprehensive overview of the challenges faced by employees and employers as they try to respond to this dramatic demographic change. Linda Duxbury and Christopher Higgins utilize an original and rich data set--gathered from 25,000 Canadians who are employed full time in public, private, and not-for-profit organizations--to demonstrate the urgent need for workplace and policy reforms and support for employed caregivers. The authors' timely work provides practical advice to managers and policy-makers about how to mitigate the effects of employee work-life conflict, retain talent, and improve employee engagement and productivity. Business and labour leaders as well as employees who truly care about their careers and industries can't afford to ignore the solutions that Something's Got to Give thoughtfully provides."--